Non-timber forest products in the global context - Shackleton, Sheona; Shackleton, C. M. (Charles Michael).; Shanley, Patricia 1955-.; SpringerLink (Online service). (Heidelberg London Springer, 2011)
This book provides a comprehensive, global synthesis of current knowledge on the potential and challenges associated with the multiple roles, use, management and marketing of non-timber forest products (NTFPs).  There has been considerable research and policy effort surrounding NTFPs over the last two and half decades. The book explores the evolution of sentiments regarding the potential of NTFPs in promoting options for sustainable multi-purpose forest management, income generation and poverty alleviation. Based on a critical analysis of the debates and discourses it employs a systematic approach to present a balanced and realistic perspective on the benefits and challenges associated with NTFP use and management within local livelihoods and landscapes, supported with case examples from both the southern and northern hemispheres. This book covers the social, economic and ecological dimensions of NTFPs and closes with an examination of future prospects and research directions.
Part 1: Introduction - Non-Timber Forest Products in the Global Context -- Non-Timber Forest Products: Concept and Definitions -- Evolving Perspectives on Non-Timber Forest Products -- Part 2: Multiple Roles and Values of Non-Timber Forest Products -- From Subsistence, to Safety Nets and Cash Income: Exploring the Diverse Values of Non-Timber Forest Products for Livelihoods and Poverty Alleviation -- Non-Timber Products and Markets: Lessons for Export-Oriented Enterprise Development from Africa -- Cultural Importance of Non-Timber Forest Products: Opportunities they Pose for Bio-Cultural Diversity in Dynamic Societies -- From the Forest to the Stomach: Bushmeat Consumption from Rural to Urban Settings in Central Africa -- Part 3: Systems for Sustainable Management of Non-Timber Forest Products -- Harvesting Non-Timber Forest Products Sustainably: Opportunities and Challenges -- Timber and Non-Timber Forest Product Extraction and Management in the Tropics: Towards Compatibility? -- Pro-Poor Governance of Non-Timber Forest Products: The Need for Secure Tenure, the Rule of Law, Market Access and Partnerships -- Non-Timber Forest Products and Conservation: What Prospects? -- Part 4: Building on the Opportunities Offered by Non-Timber Forest Products -- Regulating Complexity: Policies for the Governance of Non-Timber Forest Products -- Building a Holistic Picture: An Integrative Analysis of Current and Future Prospects for Non-Timber Forest Products in a Changing World.
Electronic reproduction.
Keywords: Non-timber forest products; Non-timber forest products industry; Sustainable forestry; Electronic books